DNA methylome and transcriptome alterations and cancer prevention by triterpenoid ursolic acid in UVB‐induced skin tumor in mice. Issue 10 (25th June 2019) - Yang, Yuqing; Yin, Ran; Wu, Renyi; Ramirez, Christina N.; Sargsyan, Davit; Li, Shanyi; Wang, Lujing; Cheng, David; Wang, Chao; Hudlikar, Rasika; Kuo, Hsiao‐Chen; Lu, Yaoping; et al.
Abstract: Nonmelanoma skin cancers (NMSCs) are the most common type of skin cancers. Major risk factors for NMSCs include exposure to ultraviolet (UV) irradiation. Ursolic acid (UA) is a natural triterpenoid enriched in blueberries and herbal medicinal products, and possess anticancer activities. This study focuses on the impact of UA on epigenomic, genomic mechanisms and prevention of UVB‐mediated NMSC. CpG methylome and RNA transcriptome alterations of early, promotion and late stages of UA treated on UVB‐induced NMSC in SKH‐1 hairless mice were conducted using CpG methyl‐seq and RNA‐seq. Samples were collected at weeks 2, 15, and 25, and integrated bioinformatic analyses were performed to identify key pathways and genes modified by UA against UVB‐induced NMSC. Morphologically, UA significantly reduced NMSC tumor volume and tumor number. DNA methylome showed inflammatory pathways IL‐8, NF‐κB, and Nrf2 pathways were highly involved. Antioxidative stress master regulator Nrf2, cyclin D1, DNA damage, and anti‐inflammatory pathways were induced by UA. Nrf2, cyclin D1, TNFrsf1b, and Mybl1 at early (2 weeks) and late (25 weeks) stages were identified and validated by quantitative polymerase chain reaction. In summary, integration of CpG methylome and RNA transcriptome studies show UA alters antioxidative, anti‐inflammatory, and anticancer pathways in UVB‐induced NMSC carcinogenesis. Particularly, UA appears to drive Nrf2 and its upstream/downstream genes, anti‐inflammatory (at early stages) and cell cycle regulatory (both early and late stages) genes, of which might contribute to the overall chemopreventive effects of UVB‐induced MNSC. This study may provide potential biomarkers/targets for chemoprevention of early stage of UVB‐induced NMSC in human.